2022
DOI: 10.15386/mpr-2053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thyroid hormones and ferritin level in patients with β- thalassemia

Abstract: Background and aims. Thalassemia is a condition that affects hemoglobin synthesis and is one of the most common hereditary illnesses in the world. Patients with thalassemia major require several blood transfusions. Multiple blood transfusions cause thyroid dysfunction, which leads to iron excess. Methods. From August 2019 to January 2020, serum samples were obtained from 90 persons, 30 of whom were healthy, and 60 (46 male and 44 female) with β-thalassemia major, aged 5-20 years, who visited the thalasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Several studies [20][21][22][23] found that severe anemia and serum ferritin levels were signi cantly associated with the incidence of hypertensive disorders, and Wang Yanxia et al [24] also indicated that high iron load causes the body to experience oxidative stress and increased vasoconstriction, leading to the development of hypertensive disorders of pregnancy. If a large amount of iron is deposited in the thyroid gland, chronic brotic changes in its substance can occur, and free iron can catalyze the formation of highly reactive oxygen radicals, leading to cytotoxicity and thyroid functional impairment [25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [20][21][22][23] found that severe anemia and serum ferritin levels were signi cantly associated with the incidence of hypertensive disorders, and Wang Yanxia et al [24] also indicated that high iron load causes the body to experience oxidative stress and increased vasoconstriction, leading to the development of hypertensive disorders of pregnancy. If a large amount of iron is deposited in the thyroid gland, chronic brotic changes in its substance can occur, and free iron can catalyze the formation of highly reactive oxygen radicals, leading to cytotoxicity and thyroid functional impairment [25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Primary hypothyroidism was found in 1.2% of our patients, which is relatively low compared to the literature. However, the onset of this disorder is generally in the second decade of life (33). Most of the patients of hypothyroidism were subclinical (16.6%); their periodic evaluation of the thyroid function was done to detect children of hypothyroidism who need thyroid replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Taher et al reported a statistically significant association between thyroid dysfunction with age and a history of splenectomy in patients with thalassemia intermedia [94]. Regular blood transfusions may lead to iron accumulation in the thyroid gland with subsequent glandular parenchyma fibrosis [56,62,95]. However, iron overload, as measured by serum ferritin, is not associated with thyroid dysfunction in several studies, despite claims to the contrary [55,56,[61][62][63]96,97].…”
Section: Hypothyroidismmentioning
confidence: 99%